Estimation of Bearing Capacity from Dynamic Cone Penetration Test in 𝒄 − ∅ Soils in Kabale Municipality. - Nkwanzi, Lillian (Kabale University, 2023)
This research project report was done to develop an empirical relationship as basis to estimate soil bearing capacity from dynamic cone penetration testing data which relates penetration resistance and bearing capacity considering frictional cohesive soils typical in proposed sites for expansion of infrastructure at kabale university, specifically Hostel construction in Kabale Municipality. The scope of investigations is limited to using dynamic cone penetrometer test, CBR testing and direct shear testing for general shear failure. For cohesive soils or soils where cohesion component can’t be neglected, which as soils typical in the area of this study, earlier proposed models of bearing capacity prediction basing on CBR are erroneous. Therefore, a relationship of bearing capacity with cohesion and DPI has been developed by linear regression. An empirical relationship has also been obtained to predict bearing capacity using DPI and cohesion from DCP and shear strength tests respectively. However, given the limited field data, further research is recommended to validate the model.